2016
DOI: 10.1038/ncomms10678
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissociation in sweet taste receptor neurons between and within taste organs of Drosophila

Abstract: Finding food sources is essential for survival. Insects detect nutrients with external taste receptor neurons. Drosophila possesses multiple taste organs that are distributed throughout its body. However, the role of different taste organs in feeding remains poorly understood. By blocking subsets of sweet taste receptor neurons, we show that receptor neurons in the legs are required for immediate sugar choice. Furthermore, we identify two anatomically distinct classes of sweet taste receptor neurons in the leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 48 publications
6
81
0
Order By: Relevance
“…In previous studies, Tsh-Gal80 and Otd-nls:FLP were successfully used to specifically suppress Gr gene expression in either the labellum or legs, respectively [37, 38]. However, both Tsh-Gal80 and Otd-nls:FLP appear to be expressed in bitter and sweet GRNs, respectively, leaving expression unaffected in a subset of IR76b-GAL4 expressing GRNs (Figure S5).…”
Section: Resultsmentioning
confidence: 95%
“…In previous studies, Tsh-Gal80 and Otd-nls:FLP were successfully used to specifically suppress Gr gene expression in either the labellum or legs, respectively [37, 38]. However, both Tsh-Gal80 and Otd-nls:FLP appear to be expressed in bitter and sweet GRNs, respectively, leaving expression unaffected in a subset of IR76b-GAL4 expressing GRNs (Figure S5).…”
Section: Resultsmentioning
confidence: 95%
“…Expression of the trans -Tango ligand in Gr64f+ GRNs revealed extensive postsynaptic signal in the CNS (Figure 5A and 5B, Movie S2). Gr64f+ GRNs are present in each leg and either terminate in the thoracic ganglia or project directly to the posterior SEZ with collaterals in the thoracic ganglia (Figure 5A) (Kwon et al ., 2014; Thoma et al ., 2016). Gr64f+ GRNs also innervate the abdominal ganglion (Movie S2).…”
Section: Resultsmentioning
confidence: 99%
“…The wide expression pattern, presence of multiple receptors in the same neurons, and different combinations of receptors in different neurons indicate that gustatory-receptor-expressing neurons in various locations may respond quite differently to different sugars (Thoma et al, 2016; Miyamoto and Amrein, 2014). We focused particularly on Gr43a-expressing neurons for their specific involvement in L-arabinose memory, and previous studies suggested they act as nutrient sensors (Miyamoto et al, 2012).…”
Section: Resultsmentioning
confidence: 99%